Bulpitt and Fletcher’s specific questionnaire for quality of life assessment of hypertensive patients - Gusmão, Josiane Lima de; Pierin, Angela Maria Geraldo (Revista da Escola de Enfermagem da USP, 2009)
This study translated and validated Bulpitt and Fletcher's Specific Questionnaire for Quality of Life Assessment of hypertensive patients. The translation and the back-translation were performed by four English teachers, and the final version was submitted to a board of referees. Questions with a Content Validity Index lower than 80% were modified and re-evaluated. The questionnaire was applied in 110 hypertensive outpatients (52 ± 8 years old, 65 % female, blood pressure 128 ± 17/75 ± 13 mmHg), which also answered the SF-36, and also in 20 normotensive people, whose characteristics were similar to those of the hypertensive subjects. The domains of SF-36 and Bulpitt and Fletcher's instrument correlated to each other (p < 0.05), except for the social aspects (r=0.07, p= 0.04) and the general state of health (r=0.04, p= 0.61). Hypertensive patients showed more positive responses to the symptoms (40%) than the normotensives (15%). The instrument was validated and is now ready to be used in our midst.